Mathematics Learning Using the Traditional Papuan Media Approach “Omtim (Sago Leaf Veins)” - Levi Pada lulu (Lembaga Penelitian dan Pendidikan Mandala, 2026)
Learning mathematics may seem boring and difficult for some, but for many, it's a knowledge that can provide solutions and significantly assist people in achieving their dreams. For example, becoming proficient in mathematics can help others gradually develop a love for learning mathematics. Mathematics is a highly abstract subject, so it's true that some people are somewhat allergic and fearful of the word, as it seems to them a threat that disrupts their lives, with numbers and formulas that are so difficult to absorb. However, it's important to realize that understanding mathematics is actually quite fascinating, as it can be done through very simple and inexpensive tools. One such tool is